Risk profiling and efficacy of albendazole against the hookworms Necator americanus and Ancylostoma ceylanicum in Cambodia to support control programs in Southeast Asia and the Western Pacific - Vito Colella, PhD; Virak Khieu, PhD; Andrew Worsley; Dammika Senevirathna, PhD; Sinuon Muth; Rekol Huy; Peter Odermatt, PhD; Rebecca J. Traub, PhD (Elsevier, 2021)
Background: Hookworm disease is endemic throughout many parts of the Asia Pacific, despite targeted control programs of at-risk populations. The success of these programs has been hindered by the limited efficacy of widely-used mebendazole, rapid re-infection rates linked to persistent reservoirs of untreated people and dogs, and the low sensitivity of conventional coprodiagnostic techniques employed.Methods: Here, we used standard faecal flotation (SFF) and a multiplex qPCR (mqPCR) assay to calculate and compare species-specific cure and egg reduction rates of single dose albendazole (400 mg) against hookworm infections at community level. Data from a cross-sectional survey in 1,232 people from Cambodia were used to inform a generalised linear mixed model to identify risk factors linked to hookworm infection(s) at baseline. Furthermore, we calculated risk factors associated to the probability of being cured after albendazole administration.Findings: Overall, 13·5% of all 1,232 people tested by SFF were positive for hookworm infection(s). Most (80·1%) infected people were >12 years of age, hence above the age targeted by the WHO control program. We estimate that as age increases, the odds of being infected increases at a faster rate for females than for males. We revealed a substantial difference in cure rate of hookworm infection(s) following albendazole treatment using the SFF (81·5%) and mqPCR (46·4%) assays, and provide the first data on the efficacy of this drug against the zoonotic hookworm Ancylostoma ceylanicum. We estimated that as age increases by one year, the odds of being cured decreases by 0·4%-3·7%. Similarly, the odds of being cured for people who boiled drinking water was estimated to be between 1·02 and 6·82.Interpretation: These findings show that the adoption of refined diagnostic techniques is central to monitoring hookworm infection(s) and the success of control strategies, which can ultimately aid in reducing associated morbidity in human populations. The approach taken is likely to be directly applicable to other parts of Southeast Asia and the Western Pacific, where specific epidemiological conditions might hamper the success of targeted treatment programs.Funding: Faculty of Veterinary and Agricultural Sciences Strategic Research Funds, The University of Melbourne.